International benchmark study on numerical simulation of flooding and motions of a damaged cruise ship. (December 2022) - Ruponen, Pekka; van Basten Batenburg, Rinnert; van't Veer, Riaan; Braidotti, Luca; Bu, Shuxia; Dankowski, Hendrik; Lee, Gyeong Joong; Mauro, Francesco; Ruth, Eivind; Tompuri, Markus
Abstract: Large cruise ships can carry 10 000 persons onboard, and consequently, survivability of the ship in the event of a flooding accident is essential. Many designers are already conducting advanced damage stability analyses beyond the regulatory requirements. With increased computing capacity, survivability analyses, by using time-domain simulation tools, are already commonly applied in the design of new cruise ships. Consequently, it is essential that such tools are properly validated, in terms of ship response and detailed flooding behavior, to assess the capability and applicability of the tools. For this purpose, an international benchmark study on simulation of flooding and motions of damaged cruise ships was conducted within the EU Horizon 2020 project FLARE, using experimental data from new dedicated model tests as a reference. The test cases include transient and progressive flooding, both in calm water and in irregular beam seas. The results indicate that capsize is properly captured by simulation codes, but there are notable differences in the flooding progression and capsize mechanisms, especially when flooding takes place in high waves.